A study on PKNS staff sensitivity towards customer satisfaction / Asmah Shaharuddin - Shaharuddin, Asmah (Faculty of Business and Management, 2005)
The Selangor State Development Corporation was established under the Selangor State Development Enactment 1964 (No.4, 1964) as a statutory body and a state development agency with the aim of reinforcing the country's independence through the distribution and fostering of socio-economic growth throughout the State of Selangor guided by government policies, in an effort to bring about stability, harmony and social justice, to realize the country's vision. This aspiration is realized through the development of property, trade and industry, as well as investment. As a dynamic and responsible corporate body, PKNS always strives to bring about continuous progress and prosperity to the State of Selangor by generating and consolidating ideas and activities for the benefit of the people besides contributing towards the creation of a united Malaysia society. All this manifested in the slogan "Progress for the People" which is always put into practice, appreciated and observed by the entire PKNS family. The purpose of the research paper is to help other organizations within this country to identify staff sensitivity in order to achieve customer satisfaction. The methodology that was used in the study was focus group (Marketing department of PKNS), where interviews were conducted in order to understand factors that influence the sensitivity towards customer satisfaction. Besides that, a 5 Likert-scale questionnaire was distributed to a small sample of marketing department in PKNS.